Quality Phytophthora de Bary and formerly named Pythium Pringsh. species isolated from woody ornamental hosts in Galician nurseries Northwest Spain - Ares, Jose Luis AndrÃ©s (Biogenesis: Jurnal Ilmiah Biologi, 2024)
.